Identification of quality problems staff vocational training - Vera V. Zhivaeva; Vadim A. Nikovaev; Svetlana N. Parfenova; Elena P. Tuponosova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Vocational training (VET) is a very complex and understudied system-object, the functioning of which is the subject to a continuous action of a large number of random (uncertain) factors. The coactions of these factors leads to significant inconsistencies in the development of the training program, reducing its effectiveness in relation to the achievement of learning objectives. The lack of commensurability of the real increase in efficiency with the target settings should be considered, first of all, as a problem of software quality. In connection with the insufficiency of the existing theoretical ideas about the internal properties of the educational process (OP), the problem of control synthesis can be solved by observing its inputs and outputs. Observation of the reaction of output quantities to changes in input influences allows us to construct an a posteriori model of the process, i.e. to identify the quality problem in the early stages of its inception.The purpose of this work is to investigate the possibility of ensuring the quality of personnel software by the identification method based on the results of evaluating the input and output signals of the OP as a control object. The methodology of work is based on the concept of integrated quality management (TQM) and the process approach.The main categories of problems of the quality of education are considered and clustered to support the adoption of managerial decisions. The most important features of closed and open problems that need to be considered when making decisions are described. Recommendations were developed on the application of methods of direct and indirect approaches to the identification of quality problems. It has been shown that discussions in cross-functional groups provide, as a rule, the best results in identifying and resolving problems. The value of the study for the theory and practice of software consists in constructing an identification procedure to support the adoption of informed decisions when choosing actions to prevent the development of quality problems.The developed identification procedure can be applied in the software system, providing an acceptable level of satisfaction of the enterprise personnel with the quality of training.